24 Improving the Investigation and Treatment of Anaemia in Older Adults Admitted Through the Acute Medical Unit. (6th February 2020) - Kaza, N; Nassour, V; Ehsanullah, J; Gravell, R; Yeoman, A; Chia, G; Todorov, G; Wright, P
Abstract: Background: This project was based within acute medical unit within a tertiary hospital in London and was conducted by junior doctors working both in geriatrics and in acute medicine. The patient group this project was aimed at was adults aged 65 and over who were admitted under acute medicine. Introduction: Anaemia is common in older adults and associated with poor outcomes. This project aimed to explore attitudes and improve recognition, investigation and management of anaemic older adults in acute medicine through a multi-pronged approach. Methods: Serial PDSA cycles were conducted over 3 months. Retrospective audit was performed, reviewing electronic records to compare a 2-week period before and after the interventions, identifying which patients admitted under acute medicine and aged over 65 years were anaemic, underwent haematinics and treatment. Interventions: Firstly, a survey explored doctors' attitudes and knowledge of anaemia in older adults as well as identifiable barriers to investigating anaemia when working in acute medicine. The data from this was used to design interventions to address the gaps which emerged. Interventions included an algorithm regarding haematinic interpretation disseminated amongst junior doctors, multiple teaching sessions conducted and posters distributed which highlighted the importance of investigating and treating anaemia. Results: The initial audit included 144 patients, of which 50 were anaemic, and the re-audit included 148 patients of which 56 were anaemic. Following the interventions, more patients had haematinics requested, from 60% to 70%, and more were treated, from 30 to 55% (p<0.05). Doctors were surveyed before and after the intervention. The repeat survey demonstrated that more doctors felt addressing anaemia was important, 83% from 55% (p<0.05). More doctors were also confident in the interpretation of haematinics, 61% from 28% (p<0.05) and in prescribing iron, 66% from 27% (p<0.05). Conclusions: Anaemia amongst elderly patients in the acute setting is under-estimated, investigated and treated. Targeted educational interventions can improve doctors' attitudes and knowledge, helping to facilitate the investigation of older adults and enable treatment.